Effect of Different Ceramic Materials on Fatigue Resistance and Stress Distribution in Upper Canines with Palatal Veneers - Tanaka, Isabela Vitelli [UNESP]; Tribst, Joao Paulo Mendes; Silva-Concilio, Lais Regiane; Bottino, Marco Antonio [UNESP] (My University, 2022)
Objective The aim of this study was to evaluate, by means of a fatigue life test, different ceramic materials used in palatal veneers to restore the canine guidance. Materials and Methods Forty-five standardized anatomical preparations were made in extracted healthy human canines with 1.2 uniform thickness. Samples were scanned, restorations were designed and milled in polymer-infiltrated ceramic network (PICN, Vita Enamic), zirconia-reinforced lithium silicate (ZLS, Vita Suprinity), and high translucent yttrium oxide-stabilized tetragonal zirconia (YZHT, Vita YZHT). Dental preparations were etched, restorations were processed according to the manufacturers' recommendations, and adhesively cemented. Then, three samples of each group were tested with load-to-fracture to determine the fatigue parameters. In addition, the palatal veneers stresses were evaluated using numerical models through finite element analysis. Results The mean of the monotonic test for PICN, ZLS, and YZHT was 674.18 N, 560.5 N, and 918.98 N, respectively. The StepWise test was performed until specimen fracture or until suspension of the test after 1.2 × 10 6cycles. Regarding survival, using the Kaplan-Meier method, PICN presented results for the mean and median of 245.21 N and 225 N, respectively; ZLS had an average of 175.76 N and a median of 168 N, and YZHT with an average of 383.30 N and a median of 366 N. Regarding the Weibull method, PICN showed results of 5.43 β and 264 η for form and scale, respectively; ZLS had 36.14 β for form and 380.67 η for scale; and YZHT presented 4.95 β for form and 417.38 η for scale. The highest stress value was calculated for YZHT, ZLS, and PICN, respectively. Conclusions It was possible to conclude that all tested materials have the possibility of being used for rehabilitation of upper canines' palatal surface.
Keywords: dental materials; dental veneers; fatigue; finite element analysis